Literary implicature: A pragmatic approach to meaning in short stories - Gofurova , Mukhlisakhon (The Lingua Spectrum, 2025)
This article explores the role of pragmatics in literary analysis, focusing on how indirect language and conversational implicature contribute to deeper meaning in short stories. Drawing on the theories of Grice, Levinson, Mey, and others, the study investigates how authors use linguistic strategies – such as elliptical dialogue, speech acts, and violations of Grice’s maxims – to shape character development and guide reader interpretation. Through a qualitative analysis of five short stories – “Hills Like White Elephants” by Ernest Hemingway, “October and June” by O. Henry, “The Birthmark” by Nathaniel Hawthorne, “The Chaser” by John Collier, and “The Appointment in Samarra” as retold by W. Somerset Maugham – the research reveals how indirect communication enriches narrative complexity and emotional depth. The findings show that authors carefully manipulate language to embed subtle clues about characters’ intentions, emotions, and internal conflicts. Pragmatic tool -implicature- not only reflects real-life conversation patterns, but also invites readers to participate actively in meaning-making. This study demonstrates that pragmatics offers a valuable framework for literary interpretation, enhancing our understanding of how language functions beneath the surface of the text.